Nuclear Recoil Calibration at Sub-keV Energies in LUX and Its Impact on Dark Matter Search Sensitivity. - Akerib,DS; Alsum,S; Araújo,HM; Bai,X; Balajthy,J; Bang,J; Baxter,A; Bernard,EP; Bernstein,A; Biesiadzinski,TP; Boulton,EM; Boxer,B; et al. (Phys Rev Lett, 2025)
Dual-phase xenon time projection chamber (TPC) detectors offer heightened sensitivities for dark matter detection across a spectrum of particle masses. To broaden their capability to low-mass dark matter interactions, we investigated the light and charge responses of liquid xenon (LXe) to sub-keV nuclear recoils. Using neutron events from a pulsed Adelphi Deuterium-Deuterium neutron generator, an in situ calibration was conducted on the LUX detector. We demonstrate direct measurements of light and charge yields down to 0.45 and 0.27 keV, respectively, both approaching single quanta production, the physical limit of LXe detectors. These results hold significant implications for the future of dual-phase xenon TPCs in detecting low-mass dark matter via nuclear recoils.